Temperature Trend Analysis for Climate Change Assessment in the South-Eastern Plateau of Jharkhand - Kumar, Ravi Ranjan; Baishya, Moumita; Kumari, Ankita; Kumar, Amit; Kumar, Avinash (International Journal of Bio-resource and Stress Management, 2026)
The present study was carried out during January, 1981 to December, 2024 in the districts (Singhbhum, East Singhbhum, and West Singhbhum) of the South-Eastern Plateau Zone of Jharkhand. In this study, the trends of air temperature were detected using the Mann–Kendall test with Sen’s slope estimator for annual and seasonal temperatures. The climatic parameters provided an ongoing need for thorough research to mitigate the unintended, severe consequences of climate change. According to past research, the trend analysis method was regarded as one of the most popular and successful approaches. Therefore, in this article, the seasonal, annual, and monthly temperatures of the Southeastern Plateau of Jharkhand were fetched and analyzed for the period interval of 44 years (1981 to 2024) by using nonparametric tests. The results obtained consisted of trend values along with trend slope and polygon graphics (arithmetic). According to the results, it was observed that the minimum temperature exhibited a significant upward trend in the spring, summer, and autumn seasons except for the winter season, while the maximum temperature displayed a downward trend in most of the seasons. The greater variability of the temperatures observed in winter seasons throughout the years.